Survival of silver diamine fluoride among patients treated in community dental clinics: a naturalistic study - Sarah E. Raskin; Eric P. Tranby; Sharity Ludwig; Ilya Okunev; Julie Frantsve-Hawley; Sean Boynes (BMC, 2021)
Abstract Background Silver diamine fluoride (SDF) is a minimally-invasive preventive service used in the U.S. to avert and arrest caries since 2014. No studies document survival outcomes based in real world delivery. We analyzed 12-month survival outcomes of SDF applied independently or concurrently with other restorative procedures among a population receiving community dental care. Methods We analyzed data on SDF applications from de-identified dental claims on Oregon Health Plan patients served by Advantage Dental in 2016, who had been seen in 2015 (patient n = 2269; teeth n = 7787). We compared survival rates of SDF alone, SDF applied with a sedative filling, and SDF with a same-day restoration. Failure was defined as a restoration or extraction of the tooth 7 to 365 days after initial application. Survival was defined as a patient returning 180 or more days after application whose tooth did not have a restoration or extraction. Differences were assessed through Wilcoxon equality of survivor function tests and log-rank equality of survivor tests to compare failure rates, Cox Proportional Hazards models to assess factors associated with survival of SDF, and Kaplan-Meier survival estimate to calculate the probability of survival over time. Results SDF alone had an overall survival rate of 76%. SDF placed with sedative filling and with a same-day restoration had survival rates of 50% and 84% respectively, likely reflecting treatment intent. SDF alone survived exceptionally well on primary cuspids, permanent molars, and permanent bicuspids and among patients aged 10 to 20 years, with modest variation across caries risk assessment categories. A single annual application of SDF was successful in 75% of cases. Among SDF failures on permanent dentition, more than two-thirds of teeth received a minor restoration. Conclusion SDF is a minimally invasive non-aerosolizing option that prevented non-cavitated lesions and arrested early decay among community dentistry patients when applied independently or concurrently with restorative procedures. Professional organizations, policy makers, providers, and payors should broaden optional SDF use by informing clinical guidelines, reimbursement policies, and treatment decisions. Future research should address clinical, social, service delivery, workforce, and economic outcomes using diverse population-based samples, and the mechanisms underlying single application success and caries prevention potential.